2024
DOI: 10.7554/elife.89298
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB2 knockdown in cervical spinal cord preserves diaphragm innervation in a mutant SOD1 mouse model of ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by motor neuron loss. Importantly, non-neuronal cell types such as astrocytes also play significant roles in disease pathogenesis. However, mechanisms of astrocyte contribution to ALS remain incompletely understood. Astrocyte involvement suggests that transcellular signaling may play a role in disease. We examined contribution of transmembrane signaling molecule ephrinB2 to ALS pathogenesis, in particular its role in driving motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that SERPINA1 [563], LRRK2 [522], CHRNA4 [564], CD22 [565], TF (transferrin) ssociated tyrosine kinase) [579], FGF14 [580], INSC (INSC spindle orientation adaptor protein) [581], BARHL1 [582], PRKCH (protein kinase C eta) [583], SLC24A4 [584], TMEM176B [585], MBP (myelin basic protein) [586], ACAN (aggrecan) [587], SHH (sonic hedgehog signaling molecule) [588], SIRT2 [589], RBP4 [590], ISM1 [591], HOXB6 [592], CDH13 [593], NTF3 [594], TRPC6 [595], MMP3 [596], HLA-DRB5 [597], HLA-DRB1 [546], CD74 [598], VWF (von Willebrand factor) [599], MDGA1 [600], ANGPT2 [601], NEDD4L [602], CASP1 [603], CHRNA5 [604], CCND2 [605], BRCA2 [606], TET1 [607], ZBTB20 [608], OAS1 [609], EGFR (epidermal growth factor receptor) [610], ABCA1 [611], PLXNA4 [612], FOXG1 [613], WEE1 [433], MAP1B [614], ANK1 [615], GRM3 [436], COMT (catechol-O-methyltransferase) [616], SLC10A4 [617], GPR39 [618] and LIFR (LIF receptor subunit alpha) [562] could promote Alzheimer’s disease progression. SERPINA1 [619], LRRK2 [620], CHRNA4 [621], TLR2 [622], MOBP (myelin associated oligodendrocyte basic protein) [623], AATK (apoptosis associated tyrosine kinase) [624], MBP (myelin basic protein) [625], SHH (sonic hedgehog signaling molecule) [626], XDH (xanthine dehydrogenase) [627], RBP4 [628], GRIA2 [629], NR3C2 [630], HLA-DRB5 [631], HLA-DRA [631], NEDD4L [632], CASP1 [633], EFNB2 [634], CYP7B1 [635], EGFR (epidermal growth factor receptor) [636], MAP1B [637], GRM3 [638<...…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that SERPINA1 [563], LRRK2 [522], CHRNA4 [564], CD22 [565], TF (transferrin) ssociated tyrosine kinase) [579], FGF14 [580], INSC (INSC spindle orientation adaptor protein) [581], BARHL1 [582], PRKCH (protein kinase C eta) [583], SLC24A4 [584], TMEM176B [585], MBP (myelin basic protein) [586], ACAN (aggrecan) [587], SHH (sonic hedgehog signaling molecule) [588], SIRT2 [589], RBP4 [590], ISM1 [591], HOXB6 [592], CDH13 [593], NTF3 [594], TRPC6 [595], MMP3 [596], HLA-DRB5 [597], HLA-DRB1 [546], CD74 [598], VWF (von Willebrand factor) [599], MDGA1 [600], ANGPT2 [601], NEDD4L [602], CASP1 [603], CHRNA5 [604], CCND2 [605], BRCA2 [606], TET1 [607], ZBTB20 [608], OAS1 [609], EGFR (epidermal growth factor receptor) [610], ABCA1 [611], PLXNA4 [612], FOXG1 [613], WEE1 [433], MAP1B [614], ANK1 [615], GRM3 [436], COMT (catechol-O-methyltransferase) [616], SLC10A4 [617], GPR39 [618] and LIFR (LIF receptor subunit alpha) [562] could promote Alzheimer’s disease progression. SERPINA1 [619], LRRK2 [620], CHRNA4 [621], TLR2 [622], MOBP (myelin associated oligodendrocyte basic protein) [623], AATK (apoptosis associated tyrosine kinase) [624], MBP (myelin basic protein) [625], SHH (sonic hedgehog signaling molecule) [626], XDH (xanthine dehydrogenase) [627], RBP4 [628], GRIA2 [629], NR3C2 [630], HLA-DRB5 [631], HLA-DRA [631], NEDD4L [632], CASP1 [633], EFNB2 [634], CYP7B1 [635], EGFR (epidermal growth factor receptor) [636], MAP1B [637], GRM3 [638<...…”
Section: Discussionmentioning
confidence: 99%